Comparative Transcriptome Analysis of Pseudomonas putida KT2440 Revealed Its Response Mechanisms to Elevated Levels of Zinc Stress - Peng, Jun; Miao, Lihong; Chen, Xi; Liu, Pulin (Frontiers in Microbiology, 2018)
The whole-genome transcriptional response of Pseudomonas putida KT2440 to stress-inducing concentrations of zinc was analyzed in this study by RNA sequencing to thoroughly investigate the bacterial cell response to zinc toxicity. The data revealed that different levels of zinc stress strongly affected the transcription of genes from the following categories: metal transport genes, genes involved in membrane homeostasis, oxidative-stress-responding genes, and genes associated with basic cellular metabolism. At the lowest zinc dose, only several genes associated with metal transport and membrane homeostasis were strongly influenced. At the intermediate zinc dose, transcriptional changes of genes belonging to these two categories were highly pronounced. In addition, the intermediate zinc stress produced high levels of oxidative stress, and influenced amino acid metabolism and respiratory chains of P. putida. At the highest zinc dose, the induction of genes responsible for Fe–S cluster biogenesis was the most remarkable feature. Moreover, upregulation of glyoxylate cycle was observed. In summary, the adaptation of the cell envelope, the maintenance of metal homeostasis and intracellular redox status, and the transcriptional control of metabolism are the main elements of stress response, which facilitates the survival of P. putida KT2440 in zinc-polluted environments.